The influence factors of mobile devices adoption among older people - Azuddin, Muna; Abd Malik, Sofianiza; Abdullah, Lili Marziana (IGI Global, 2018)
This article describes how the use of mobile devices has huge potential in assisting mobile users to perform everyday tasks. However, there is a small percentage of older people that uses mobile devices. This shows that, there are several factors that influenced the small group of older people to adopt the technology. In addition, there have been limited studies that investigate factors that influenced older people to adopt mobile devices. This article aims to understand the causes that have encouraged older people to adopt such technology. Qualitative methods including interview and focus groups were conducted among twenty-one older people aged 55 and above. The results indicated that, there were five factors that influenced older people to use mobile devices. These factors were mobile device design, functions, social inspiration, economical and other related factors.